Tradisi Cin Peddis Pada Bulan Muharram di Lingkungan Etnis Madura di Kalimantan Barat - Musa, Dahniar Tahir; Muhammad Haiyun; Ignasia Debbye Batuallo (Farabi, 2024)
The tradition of cin peddis in the madurese community has become a symbolic tradition in West Kalimantan. This tradition was inherited by the ancestors of the madurese tribe in the tradition of local community customs. Those who carry out the cin peddis tradition perform customs as a form of local knowledge in the community. Uniquely, the cin peddis tradition is carried out in the month of Muharram to preserve the local traditions of the madurese community. This research formulates the question of how the symbolic interpretation of the cin peddis tradition in Muharram month in the environment of the madura ethnic group in West Kalimantan. This research uses ethnographic method with the theory of symbolic interpretative approach. The results of this study show that: (1) the existence of morality values in the cin pendis tradition symbol; (2) the existence of religious values in the spirituality of the community performing the cin pendis tradition; (3) the existence of kinship values in the madura ethnic community. Thus, interpretative symbol tradition appears in the cin peddis tradition in the Madurese community of West Kalimantan.